Predicting the Dielectric Response of Saturated Sandstones Using a 2-electrode Measuring System - Kirichek, Alex; Chassagne, Claire; Ghose, Ranajit (Frontiers in Physics, 2019)
4-electrode setups are usually used to measure the dielectric response (complex conductivity)of sandstones, as it is known that 2-electrode systems are sensitive to unwantedelectrode polarization at low frequency. Moreover, electrode polarization (EP) occurs inthe frequency range where the characteristic relaxation associated to the grain size also occurs, which can therefore theoretically be assessed using 4-electrode setups. Nonetheless, we find that other parameters of interest (porosity, salinity) can easily be extracted from the frequency range 1 - 10 kHz, beyond the one affected by EP using a 2 electrode setup. An additional unwanted effect (”pseudo-inductance”) is observed in the frequency range 10 kHz - 1 MHz during our experiments. Even though the origin of this effect remains unknown, it is shown to be correlated with the ionic strength of the system and the electrode separation. The bulk polarization region, i.e. the region of intermediate frequencies devoid of EP and pseudo-inductance polarizations, is the one of interest, as the complex conductivity of the system is there only dependent on material parameters such as the porosity of the sandstone and the conductivity of the electrolyte. We demonstrate that in the bulk region the model predicts the complex conductivity response, when these porosity and ionic strength are known. The model has been validated using laboratory measurements on a Bentheim sandstone saturated with five different NaCl concentrations: 5 mM, 10 mM, 100 mM, 170 mM and 540 mM.